Indonesian and Tunisian Constitutional Frameworks: The Impact on the Development of Higher Education Curriculum - Ulpah, Mariam (Muslim Education Review, 2022)
Education has a critical role in the development of a new generation of individuals. It all depends on the constitutional frameworks and norms around which educational institutions and educational praxis are founded, and education is one of the tools to maintain national identity. The quality of education cannot simply be measured by the percentage of GDP spent on education. According to the World Data Bank, Tunisia spends 26.63 percent of its budget on education, while Indonesia spends only 20.50 percent. However, this does not guarantee that the quality of education in Tunisia is higher than in Indonesia due to the cultural and constitutional framework disparities between the two countries. The aim of this study is to compare the higher education curricula in Tunisia, which was developed from the French secular, or laicite, system, with that in Indonesia, which is founded on the ideology of Pancasila. Moreover, this study aims to analyze how the laicite system and Pancasila ideology have an impact on higher education curriculum design. The method used is a qualitative approach with a comparative case study analysis. Data was obtained from interview sessions with policy makers on curriculum as well as from the handbooks of curriculum in the Faculty of Culture at Indonesia University and the curriculum of the Faculty of Humanities and Social Sciences at Tunis University and focuses on the learning method and outcomes, as well as other journal and mass media pieces that are relevant. The data shows that disparities between constitutional frameworks and ideological contrasts between Pancasila and the laicite system have a significant impact on the religious component of the curriculum development process. In Tunisia, in particular, the curriculum has yet to achieve the government’s goal of developing critical consciousness. In Indonesia, the curriculum is based on the process model design, while in Tunisia, it is based on the product model design.